ENHANCING STUDENTS' READING ABILITY THROUGH CNA INDONESIA - Ali, Syahban Mada (JURNAL NALAR PENDIDIKAN, 2020)
The aim of this research is to find out whether the students’ reading ability improve or not through CNA Indonesia at the fourth semester Students of Tomakaka University of Mamuju. The method was used is quantitative method. The instrument used to collect the data was reading test. The number of test consisted of 15 and the form is multiple choices. The subject of this research was the fourth semester students of Tomakaka University of Mamuju. In analyzing the data collected through quantitative analysis. The result of this research is the use of Channel News Asia (CAN) Indonesia can enhancing the students’ reading ability at the fourth semester students of Tomakaka University of Mamuju. It is supported by the result of the test which given for the students after given treatment. The result showed that there was an improvement significantly between pre-test and post-test